Mechanical behavior and acoustic emission evolution of cracked red sandstone under uniaxial compression - Yao, Rong; Jinzhi, Liu; Xianjie, Peng; Yang, Sun; Kui, Wang (Frontiers in Built Environment, 2025)
The analysis of crack morphology have important influences on the study of rock mechanical properties and crack propagation behavior. A series of uniaxial compression tests and acoustic emission (AE) tests were conducted on different crack forms of red sand stone (intact rock specimens and single cracked and double cracked specimens). The results show that: 1) Intact rock specimens exhibit higher peak stress, peak strain, and elastic modulus than cracked specimens. Peak stress and elastic modulus are significantly affected by crack configuration, while peak strain differences are relatively minor. Single cracked specimens demonstrate higher peak stress and elastic modulus compared to double crack specimens. 2) During the yield stage and post-peak failure stage, both single and double cracked specimens exhibited distinct AE ringing count and cumulative ringing count surges with increasing fracture inclination angle. The AE ringing counts show a “step-like” growth pattern, while the proportion of cumulative ringing counts increases logarithmically with the inclination angle. 3) Analysis of the failure modes reveals that, with increasing crack inclination angles, single cracked specimens predominantly undergo shear–tensile mixed failure, whereas double cracked specimens progressively evolve from shear tensile mixed failure to tensile failure. These findings provide experimental evidence for assessing crack rock mass stability and predicting failure mechanisms.